MODEL INFILTRASI PADA BERBAGAI PENGGUNAAN LAHAN DI DESA TULO KECAMATAN DOLO KABUPATEN SIGI - Yunagardasari, Cindy; Paloloang, Abdul Kadir; Monde, Anthon (AGROTEKBIS, 2017)
This study aims to determine the model of infiltration at a variety of land uses (land palm plantations, cocoa plantation land, wetland and shrub land) in the village of Tulo, District Dolo, Sigi. Data analysis infiltration rate equation model Horton. Infiltration rate measurements in Â Â Â Â Â Â Â Â the field using a double ring infiltrometer are embedded into the ground and then ring in Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â the contents above water until the boundary line. Observation of decreased water level in measuring each interval of 10, 20,30,40,50,60 minutes. Measurement of infiltration repeated three times Â Â Â Â Â Â Â for each land use. The results showed that the model of infiltration in oil plantation area that Â Â Â Â Â Â Â Â Â Â Â is f = 8,2 + (10 â 8,2) e-2,64t, on a cocoa plantation land is f = 8 + (10 - 8) e-2,68t, in paddy fields, namely f = 9,23 + (10 â 9,23) e-5,20t and the shrub land is f = 4 + (10 - 4) e-2,96t. Infiltration in the shrub land quite a bit faster in the amount of 6,56 cm/hour, on a cocoa plantation land classified as being in the amount of 2,06 cm/hour, on a coconut plantation land and wetland quite a bit slower with the infiltration rate of the soil palm plantations amounted to 1,87 cm/hour and a wetland ofÂ Â Â Â Â Â Â Â Â Â Â Â Â 0,87 cm/hour.Â Key Words : Cocoa plantation land, Desa Tulo, infiltration rate, land coconut plantation, shrub land, wetland.